The Effect of Mental Health and Workload Management on Students' Motivation During the Undergraduate Thesis Writing Process: Evidence from the Faculty of Economics and Business, Universitas Padjadjaran - Alicia Amara Suryo; Yunizar Yunizar (Greenation International Journal of Tourism and Management, 2026)
The undergraduate thesis writing process constitutes one of the most challenging phases of higher education, as it requires students to demonstrate not only academic capability but also emotional stability and effective workload management skills. Although previous research has extensively explored the individual effects of mental health or academic workload on students' academic performance, limited empirical studies have investigated the combined influence of these factors on students' motivation throughout the thesis writing process, particularly in the context of Indonesian universities. This study seeks to analyze the impact of mental health and workload management on students' motivation while completing their undergraduate thesis at the Faculty of Economics and Business, Universitas Padjadjaran. Using a quantitative explanatory research design, data were collected through a survey involving 313 undergraduate students who were actively engaged in writing their thesis. Participants were selected using a stratified random sampling method, and the data were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4. The results reveal that mental health exerts a positive and statistically significant influence on students' motivation. Likewise, workload management has a positive and significant effect, with a greater contribution to motivation compared to mental health. Collectively, both independent variables account for 50.1% of the variance in students' motivation during the thesis writing process. The primary contribution of this study is the development of an integrated structural model that combines mental health and workload management to explain students' motivation in undergraduate thesis completion, offering empirical evidence from Indonesian higher education and expanding prior research that has generally examined these variables independently.